A solid‐shell corotational element based on ANDES, ANS and EAS for geometrically nonlinear structural analysis. (28th May 2013) - Mostafa, M.; Sivaselvan, M.V.; Felippa, C.A.
SUMMARY This paper describes an eight‐node, assumed strain, solid‐shell, corotational element for geometrically nonlinear structural analysis. The locally linear kinematics of the element is separated into in‐plane (which is further decoupled into membrane and bending), thickness and transverse shear components. This separation allows using any type of membrane quadrilateral formulation for the in‐plane response. Assumed strain fields for the three components are constructed using different approaches. The Assumed Natural Deviatoric Strain approach is used for the in‐plane response, whereas the Assumed Natural Strain approach is used for the thickness and transverse shear components. A strain enhancement based on Enhanced Assumed Strain concepts is also used for the thickness component. The resulting element passes well‐known shell element patch tests and exhibits good performance in a number of challenging benchmark tests. The formulation is extended to the geometric nonlinear regime using an element‐independent corotational approach. Some key properties of the corotational kinematic description are discussed. The element is tested in several well‐known shell benchmarks and compared with other thin‐shell and solid‐shell elements available in the literature, as well as with commercial nonlinear FEM codes. Copyright © 2013 John Wiley & Sons, Ltd.